PERISTILAHAN PROSES PERKAWINAN ADAT DAYAK BADAMEA BINUA GAJEKNG KABUPATEN BENGKAYANG - Dira, Hyachinta; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Customary marriage is a traditional wedding ceremony that has been carried out for generations in Samalantan Village Binua Gajekng Bengkayang Regency. The problem in the research is how the inventory of terminology in traditional marriage, lexical meaning, cultural meaning, and semantic function. This study aims to describe the terminology in the traditional marriage process of the Dayak Badameay. The method used in this research is descriptive research method with qualitative research form. The data source in this research is Badamea Dayak language. The data in this study are the form of terminology of the traditional marriage process. The data collection technique used open chitchat technique, recording technique, and note-taking technique. The results of the analysis carried out based on the problems in the study which include pre-implementation, implementation, and post-implementation terminology. This research describes the form of inventory of terminology, lexical meaning, cultural meaning, and semantic function.   Based on data analysis, there are 54 data of terminology in the traditional marriage process of Dayak Badamea Binua Gajekng Bengkayang Regency. The lexical meaning amounted to 53 data, the cultural meaning amounted to 21 data, and the semantic function amounted to 54 data.